Perbandingan kualitas dokumentasi keperawatan berbasis elektronik dan berbasis kertas: Study literature - Tomy Suganda; Rr Tutik Sri Hariyati (Holistik Jurnal Kesehatan, 2020)
Paper‐based versus electronic‐based of health records in quality of nursing documentation: A literature review study.Background: Many technological developments in nursing services have emerged, one of them is electronic-based nursing documentation. The electronic nursing documentation has a good impact which increases the quality of service. But the readiness is still questionable.Purpose: Describing the quality comparison of electronic-based nursing documentation and paper-based nursing documentation.Method: This study uses a PRISMA literature review. Through the remote-lib.ui.ac.id database that is connected to various scientific publication pages such as, Scopus, Ebsco, PROQUEST Scholar-Articles with several key words such as electronic nursing documentation, nursing paper documentation, management information systems.Results: Electronic-based documentation has a higher level of quality documentation than paper-based documentation in terms of efficiency, effectiveness, patient focus and timeliness.Conclusion: Electronic-based documentation offers the optimization of nursing care, effective and efficient documentation, integrated nursing care and cost-effective through (paperless). Strong support from hospital institutions, organizations and government at the beginning of the nurse adaptation system and process is a challenge so that the application of electronic nursing documentation is realized properly.Keywords: Paper‐based; Electronic‐based; Health records; Quality; Nursing documentation.Pendahuluan: Pengembangan teknologi dalam pelayanan keperawatan banyak bermunculan, salah satunya dokumentasi keperawatan berbasis elektronik. Dokumentasi keperawatan elektronik memberikan dampak baik yang luarannya meningkatkan kualitas pelayanan. Namun kesiapan masih dipertanyakan.Tujuan: Menggambarkan perbandingan kualitas dokumentasi keperawatan berbasis elektronik dan dokumentasi keperawatan berbasis kertas.Metode: Penelitian ini menggunakan tinjauan pustaka PRISMA. Melalui Database remote-lib.ui.ac.id yang terhubung dengan berbagai macam laman publikasi ilmiah seperti, Scopus, Ebsco, PROQUEST, Scholar-Artikel dengan beberapa kata kunci seperti dokumentasi keperawatan elektronik, dokumentasi keperawatan kertas, sistem informasi manajemen.Hasil: Dokumentasi berbasis elektronik memiliki tingkat kualitas dokumentasi lebih dibandingkan dokumentasi berbasis kertas secara efesiensi, efektifitas, fokus pada pasien maupun ketepatan waktu.Simpulan: Dokumentasi berbasis elektronik menawarkan keoptimalan melakukan asuhan keperawatan, dokumentasi efektif dan efesien, asuhan keperawatan terintegrasi serta cost-effective melalui (paperless). Dukungan kuat dari institusi rumah sakit, organisasi maupun pemerintah dalam permulaan sistem dan proses adaptasi perawat menjadi tantangan, agar penerapan dokumentasi keperawatan elektronik terealisasi dengan baik.